Reagent-controlled regiodivergent ring expansions of steroids - Manwika Charaschanya (Nature Portfolio, 2018)
Late-stage diversification of natural products is an important starting point for drug discovery. Here, the authors use chiral reagents to perform the regiocontrolled ring expansion of steroid precursors and achieve more than 100 isomerically pure analogs with spatial and functional diversity.